State-led modernization of the Ethiopian sugar industry: questions of power and agency in lowland transformation - Yidneckachew Ayele Zikargie (16946634) (2022)
This article critically analyses the history of the Ethiopian sugar industry, with emphasis on drivers, decision-making and processes of incorporation and exclusion aiming to transform lowlands. We argue that the government has used a state-led modernization and expansion of the sugar industry to consolidate the power of central governments. Through the creation of sugar-based agribusinesses, the changing regimes have sought to extend their control over natural resources, increase the movement of labour, and stimulate economic growth. This has led to deepened state structures and considerable transformation of power relations, causing marginalization of the affected communities. In Ethiopia’s post-2018 political and economic transition, this modernist and expansionist programme found itself in a set of deep economic and financial crises, leading to government initiatives to privatize the sugar industry. In response to the privatization initiatives, local elites articulate and contest the historical process of marginalization and compete in demanding redress for the adverse incorporation of the communities. They do so to expand the community space for agency and enforce their interests in gaining from, and perhaps dominating a privatization process through takeover strategies. The past modernist development approach that caused marginalization is likely to affect a new stage of lowland transformation. Other Information Published in: Journal of Eastern African Studies License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/17531055.2023.2166449